Stem Cell Transplantation Efficacy in Cerebral Palsy: A Case Report from a Physical Therapist Perspective - Kora, Alaa Noureldeen (BioScientific Review, 2021)
Children with spastic cerebral palsy usually display an elevationin muscle tone,a decline in gross motor functional abilities,feeding problems and visual problems.Studies on stem cell treatment are in their early stages concerningitsefficacy forcerebral palsy. The purpose of the current study was to evaluate the efficacy of stem cell transplantation forgross motor functions, fine motor functions, feeding, visionandspasticity in achild with cerebral palsy(CP). A child with spastic CPon Level Vofthe Gross Motor Function Classification System(GMFCS)was selectedforthe transplantation of autologous Bone Marrow-derived Mononuclear Cells(BMMNCs). Muscle tone, grossmotor abilities, finemotor abilities, feeding abilities and visual abilities were assessed on 4 occasionsincluding1)beforethe transplantation,2) immediately after the transplantation,3) sixmonths after the transplantation,and 4) oneyearafter the transplantation.No effect of stem cell transplantation was observedinthe childconcerning gross motor functions, fine motor functions,feeding, vision and the degree of spasticity. Furtherstudies should be carried out on the subject using a different population rather than the one comprising children on Level V of the GMFCS. Keywords: autologous, cerebral palsy (CP), children, stem cells Copyright (c) The Author